Ivory Gull Colonies on the Devon Island Ice Cap, Arctic Canada - Frisch, Thomas (ARCTIC, 1983)
Four small Ivory Gull colonies have been found on nunataks on the ice cap of eastern Devon Island. Mainly on the basis of their similarity to known breeding places of the Ivory Gull on Ellesmere Island, all four sites are believed to be those of nesting colonies the first to be reported from Devon Island.Key words: Ivory Gull, Pagophila eburnea, colonies, nunatak nesting sites